Pretreatment for Bilateral Nephroblastomatosis is an Independent Risk Factor for Progressive Disease in Patients with Stage V Nephroblastoma - Furtwängler, R.; Schmolze, M.; Gräber, S.; Leuschner, I.; Amann, G.; Schenk, J.-P.; Niggli, F.; Kager, L.; Schweinitz, D. v.; Graf, N. (Klinische Pädiatrie, 2014)
Background: Treatment of stage V nephroblastoma is less established and more complex than in unilateral nephroblastoma.Methods: Retrospective analysis of 121 consecutive patients with stage V nephroblastoma registered from January 1989 to May 2005. Registration, prospective data collection and treatment were carried out within the framework of 3 consecutive SIOP/GPOH-nephroblastoma-trials.Results: 19 patients had metastasis and 29 syndromes at diagnosis. 13 patients had been pretreated for bilateral nephroblastomatosis. 1 patient was not treated and 17 patients had upfront surgery. Preoperative treatment duration ranged from 1–12 weeks (n=103). 1–3 preoperative treatment-cycles resulted in average tumor-volume-reduction of 45%. 1 patient underwent bilateral nephrectomy. 52% of the patients had 2 functioning kidneys after the end of treatment. 20 patients had died after mean follow-up of 8.6 years. 5y-Progression-Free (PFS) and Overall-Survival (OS) were excellent for patients having a localized disease without pretreatment for nephroblastomatosis (5yPFS/OS: 80±4%/93±3%). Metastasis at diagnosis (51±12%/56±12%; p=0.003) and pretreatment for nephroblastomatosis (37±14%/67±13%; p<0.001) were associated with significantly poorer outcome. Cox-regression analysis revealed an independent influence of pretreatment for nephroblastomatosis, metastasis and syndromes on PFS. The latter 2 as well as anaplasia and age (<2 years or >3 years) had an independent influence on OS.Conclusions: Pretreatment for nephroblastomatosis, metastasis and syndromes are independent risk factors. 1–3 preoperative treatment-cycles are sufficient to achieve save nephron-sparing-surgery in most patients.
Keywords: nephroblastoma; bilateral; stage V; SIOP; metastasis; stage IV